Prevalence and Risk Factors for Thrombotic Complications Following Venovenous Extracorporeal Membrane Oxygenation: A CT Scan Study*. Issue 2 (February 2020) - Parzy, Gabriel; Daviet, Florence; Persico, Nicolas; Rambaud, Romain; Scemama, Ugo; Adda, Mélanie; Guervilly, Christophe; Hraiech, Sami; Chaumoitre, Kathia; Roch, Antoine; Papazian, Laurent; Forel, Jean-Marie
Abstract : Objectives: The aims of this study were to: 1) analyze the cannula-associated deep vein thrombosis frequency after venovenous extracorporeal membrane oxygenation using a CT scan and 2) identify the associated risk factors for cannula-associated deep vein thrombosis. Design: Retrospective observational analysis at a single center. Setting: Tertiary referral university teaching hospital. Patients: Patients under venovenous extracorporeal membrane oxygenation with a femorofemoral or femorojugular cannulation admitted for acute respiratory distress syndrome or primary graft dysfunction after pulmonary transplantation. CT scan was performed within 4 days after decannulation. Interventions: None. Measurements and Main Results: We included 105 of 228 patients screened. Bacterial pneumonia was the main indication of venovenous extracorporeal membrane oxygenation (46.7%). CT scans were performed at a median of 2 days (1–3 d) after decannulation. Cannula-associated deep vein thrombosis was found in 75 patients (71.4%) despite it having a mean activated partial thromboplastin time ratio of 1.60 ± 0.31. Femorofemoral cannulation induced femoral cannula-associated deep vein thrombosis more frequently than femorojugular cannulation (69.2% vs 63.1%, respectively; p = 0.04). Seventeen of the 105 patients (16.2%) had a pulmonary embolism. Multivariate logistic regression analysis showed that higher the percentage of thrombocytopenia less than 100 G/L during extracorporeal membrane oxygenation period, lower the risk for developing cannula-associated deep vein thrombosis (hazard ratio, 0.98; 95% CI, 0.98–1.00; p = 0.02). Conclusions: Cannula-associated deep vein thrombosis after venovenous extracorporeal membrane oxygenation is a frequent complication. This plead for a systematic vascular axis imaging after venovenous extracorporeal membrane oxygenation. Thrombocytopenia is associated with a reduction in the occurrence of thrombotic events. Abstract : Supplemental Digital Content is available in the text.